(untitled) (Scientific Conference on Multidisciplinary Studies, 2025)
Pumps are hydraulic machines widely used in various fields. There are different types of pumps depending on the area of application, and centrifugal pumps are among the most common. Over time, pumps face various problems and require technical maintenance. Among them, impeller wear is one of the most common issues that reduce pump efficiency. Cavitation, corrosion, and erosion are also major problems encountered in centrifugal pumps. To minimize these problems, frequent maintenance strategies are required. Many researchers have used different methodologies to address these issues. This work presents various problems observed in centrifugal pumps and their causes.